2007
DOI: 10.2203/dose-response.06-011.mothersill
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Bioelectric Effects in the Induction of Bystander Signals by Ionizing Radiation?

Abstract: The induction of "bystander effects" i.e. effects in cells which have not received an ionizing radiation track, is now accepted but the mechanisms are not completely clear. Bystander effects following high and low LET radiation exposure are accepted but mechanisms are still not understood. There is some evidence for a physical component to the signal. This paper tests the hypothesis that bioelectric or biomagnetic phenomena are involved. Human immortalized skin keratinocytes and primary explants of mouse bladd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 43 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…This effect has been demonstrated for both high-and low-linear energy transfer radiations, but it is usually larger for densely ionizing radiation such as α particles [44]. Interestingly, 10 min exposure to static and time-varying MFs generated by a standard 1.5 T MRI device, as typically set to perform a routine head scan protocol, induce a bystander response in human adherent epithelial cells derived originally from a foreskin primary culture and immortalized by the HPV virus (HPV-G cells) [45]. As shown in Figure 2, human myeloid leukaemia U937 cells undergo blebbing of their plasma membrane when cultivated for up to 6 h in conditioned medium harvested from PBLs that previously had been left under exposure for 24 h to a SMF of 6 mT.…”
Section: Incidence On Intercellular Communicationsmentioning
confidence: 99%
“…This effect has been demonstrated for both high-and low-linear energy transfer radiations, but it is usually larger for densely ionizing radiation such as α particles [44]. Interestingly, 10 min exposure to static and time-varying MFs generated by a standard 1.5 T MRI device, as typically set to perform a routine head scan protocol, induce a bystander response in human adherent epithelial cells derived originally from a foreskin primary culture and immortalized by the HPV virus (HPV-G cells) [45]. As shown in Figure 2, human myeloid leukaemia U937 cells undergo blebbing of their plasma membrane when cultivated for up to 6 h in conditioned medium harvested from PBLs that previously had been left under exposure for 24 h to a SMF of 6 mT.…”
Section: Incidence On Intercellular Communicationsmentioning
confidence: 99%
“…These are caused by as yet poorly defined factors released by irradiated cells and include chromosomal aberrations and instability, sister chromatid exchanges, mutagenesis, micronucleation, cell death, changes in transcription and enzyme activities, and sometimes increased proliferation, differentiation, and neoplastic transformation (1)(2)(3)(4)(5)(6). Some studies implicate direct intercellular connections (gap junctions) in these processes (7)(8)(9)(10), whereas others show participation of cytokines or other factors secreted into the culture medium (11)(12)(13) or of physical factors (14). A role of reactive oxygen species (ROS) and nitrogen species and calcium signaling appears to be established; irradiated cells produce ROS and nitrogen species, whereas antioxidants or voltage-dependent calcium channel blockers reduce bystander effects (11,(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of chip technology and advanced proteomics techniques, screening for relevant proteins and miRNAs became possible [62]. The second breakthrough was when it was shown that irradiation of organic matter (shells, fruits or cells) led to biophoton emission in the UVA range and that there seemed to be a physical component to the initial bystander signal [63][64][65][66]. A series of papers [67][68][69] linked the photon emissions to the extent of the BE and implicated both p53 and exosomes in the mechanism.…”
Section: B Possible Reasons/mechanismsmentioning
confidence: 99%